2004
DOI: 10.1002/jnr.20016
|View full text |Cite
|
Sign up to set email alerts
|

Axotomy‐dependent and ‐independent synapse elimination in organ cultures of Wlds mutant mouse skeletal muscle

Abstract: Progressive "dying back" neurodegenerative diseases are debilitating due to loss of connectivity after nerve terminal and axonal withdrawal, which impairs peripheral nerve function and leads ultimately to neuronal cell death. The mutant mouse (Wallerian degeneration slow; Wld s ) provides an accessible model system to understand orthograde and retrograde degeneration, because in these mice axotomy induces slow, progressive withdrawal of nerve terminals from motor endplates. Axon degeneration itself is about 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Significantly, during the course of these studies we found no evidence of gross, injury-induced degenerative events up to and including 5 hr after axons were cut during dissection. This agrees with our previous findings which indicated that Wallerian degeneration does not begin until at least 12 hours after dissection [ 6 ]. Specifically, we saw no evidence of terminal Schwann cells engulfing degenerating nerve terminal boutons in-situ, mitochondrial degradation or cytoplasmic vacuolation [ 32 , 38 ], which would indicate degenerative events.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Significantly, during the course of these studies we found no evidence of gross, injury-induced degenerative events up to and including 5 hr after axons were cut during dissection. This agrees with our previous findings which indicated that Wallerian degeneration does not begin until at least 12 hours after dissection [ 6 ]. Specifically, we saw no evidence of terminal Schwann cells engulfing degenerating nerve terminal boutons in-situ, mitochondrial degradation or cytoplasmic vacuolation [ 32 , 38 ], which would indicate degenerative events.…”
Section: Discussionsupporting
confidence: 94%
“…In these experiments we show that a brief pharmacological signal can trigger rapid and significant morphological events in cell fragments consisting of isolated nerve terminals and attached distal axon stumps. We suggest that the morphology of these events most closely resembles nerve terminal retraction during developmental synapse elimination [ 4 , 6 , 33 , 36 ], following nerve section in the slow Wallerian degeneration mouse [ 6 ] and in motor neurone disease [ 17 ]. We also observed fragmentation of pre and/or postsynaptic sites at a small number of neuromuscular junctions and interestingly similar synaptic responses have also been observed during developmental synapse elimination [ 37 ] and in mouse models of spinal muscular atrophy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified nerve terminal morphologies indicative of Wallerian-like fragmentation processes as well as asynchronous nerve terminal retraction. Although nerve terminal retraction is normally a mechanism of loss associated with developmental synapse elimination (Sanes & Lichtman, 1999;Keller-Peck et al 2001;Gillingwater et al 2002;Walsh & Lichtman, 2003;Parson et al 2004), there are increasing numbers of reports showing that withdrawal can occur in response to injury and disease in adult motor nerve terminals (Gillingwater et al 2002;Fischer et al 2004;Bettini et al 2007;Murray et al 2008). The finding that nerve terminal function may be disrupted in advance of disassembly suggests that future experiments are required to define accurately the spatio-temporal characteristics of hypoxiareperfusion injury.…”
Section: Discussionmentioning
confidence: 99%